Prevalence of Gestational Diabetes Mellitus and main Immeditely Complicatin after Delivery in River Nile state (Atbara , Eldamer , Berber , Sulaa) Hospitals - Abdelrahman mohammed saeed; Aisha abazer hassan; Areej mohammed hassan; Badreldeen elkashif ali; Marnia nabil adly; Najat adel maki; Riham elfadil abdelmuty (جامعة الشيخ عبدالله البدري, 2018)
ABSTRACT: Back ground: HIV is major public health problem globally the study aimed to estimating the prevalence of HIV among pregnant women in River Nile state during period from (March-July) 2018. Objective: to assess prevalence of HIV in pregnant women in River Nile State. Method: this study is descriptive hospital base study design in River Nile state, north of Sudan, population in this study estimated to be more than one million people among pregnant women attending delivery room includes 384 pregnant women, through prepare questionnaire by take secondary data from delivery room after consent from pregnant labor. Result: the data will be managed by SPSS by statistic program windows. Out of 384 pregnant women 7 found to be HIV positive with sero prevalence rate of 1, 8. Majority of sero positive women (18,5%) were done tattoo procedure and secondary educational level (36.2%). Conclusion: The study conclude that prevalence of HIV among pregnant women in river Nile Stat were low among those under growing test of HIV as routine investigation even normal delivery and cesarean scion according our risk factor of HIV based on our analysis significant between tattoo and level of education.